The Efficacy and Safety of Dexmedetomidine and Propofol Versus Midazolam Alone in Adult Patients Undergoing Endobronchial Ultrasound-guided Transbronchial Needle Aspiration: a Retrospective Analysis - Tei, Yoshitaka; Katakura, Seigo; Hirama, Nobuyuki; Kamimaki, Chisato; Aiko, Hiroko; Kudo, Makoto; Kubo, Sousuke; Kaneko, Takeshi; Yamamoto, Masaki; Mikami, Naoto (The Journal of the Japan Society for Respiratory Endoscopy, 2019)
Background. Midazolam is the most frequently used sedative in addition to topical anesthetics for flexible bronchoscopic procedures, including endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA), in Japan. However, cough caused by airway irritation sometimes make it difficult to conduct these procedures, especially EBUS-TBNA, with midazolam. Recent reports have shown that the combination of various pharmacological sedatives results in favorable responses for both patients and bronchoscopists. Purpose. To evaluate the superiority of sedation with propofol and dexmedetomidine in comparison to midazolam alone during EBUS-TBNA. Patient and Methods. Thirty-nine patients who had undergone EBUS-TBNA from June 2016 to December 2017 at Yokohama City University Medical Center were enrolled. Subjects who received only EBUS without TBNA were excluded. All EBUS-TBNA procedures were performed after intubation using a conventional bronchoscope. The examination time, diagnosis rates, and frequency of adverse events in the propofol and dexmedetomidine (PD) group were retrospectively compared with those in the midazolam (M) group. Results. Although the number of punctures were not significant, the time required per puncture was significantly shorter in the PD group than in the M group. As a result, the time to complete EBUS-TBNA procedures was significantly shorter in the PD group than in the M group (19.4±7.9 vs 34.2±9.7 min, p<0.0001). The frequency of adverse events was lower in the M group than in the PD group, although no severe events were observed in either group. Conclusion. Sedation with propofol and dexmedetomidine during EBUS-TBNA reduced the examination time and was safe under appropriate monitoring and supportive therapies.